Design of Protection Mechanisms for the Internet of Drones - Svaigen, Alisson R.; Ruiz, Linnyer B.; Loureiro, Antonio A. F. (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2024)
The Internet of Drones (IoD) emerged as a novel mobile network paradigm. IoD is a unique environment with particular characteristics that differ from traditional ones (e.g., drones’ mobility and the fast network topology change), demanding compliance with security and privacy requirements. Likewise, IoD can suffer from novel drone-centered threats. The existent protection mechanisms (PMs) may not be adequate for the IoD environment since they may not embrace the IoD characteristics, also facing new threats. Therefore, the main goal of this dissertation is to study the design of PMs for the IoD, considering its particular characteristics. This study reveals a need to enhance current PMs to meet the IoD characteristics since they can not offer the same protection level. Our contributions advance the state-of-the-art on four fronts: new guidelines for IoD security and privacy field; novel location privacy PMs; novel anti-jamming PMs; and new strategies for automatic drone detection.